ANALISIS PRODUKSI DAN PEMASARANBATIK JUMPUT DESA METATU KECAMATAN BENJENG KABUPATEN GRESIK - Azmy, Bahaudin (Jurnal Penamas Adi Buana, 2017)
Cassava roll sausage cheese is one of a snack delicious made of the main ingredient cassava.Besides it can also served as a breakfast and provision children to school practical. It also can be presented as a breakfast and provision children to schools that practical .The majority work the people at deliksumber are farmers, and estate crops. But some are unemployed, in this case a housewife only hope the income husband. Cassava roll into one of the answers mother's these households, with the training given by students to mother's Deliksumber. To obtain the desired data and in accordance with the existing problems in the manufacture of cassava rolls, then we use two methods are able to support these activities. Namely the observation and documentation, where the observation is a system or plan for behavioral assessments.In this observation, researchers directly involved in the or situation observed as data sources analysis where related production and marketing cassava roll in the village deliksumber in benjeng gresik district. Documentation used for collecting additional data of the written and related analysis of production and marketing cassava roll in the DesaDeliksumber in Kecamatan Benjeng Kabupaten Gresik hat all it is giving information for researched process .